2019
DOI: 10.3168/jds.2019-16601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in-feed enzymes on milk production and components, reproduction, and health in dairy cows

Abstract: Our objectives were to characterize responses in the field to a mix of fibrolytic enzymes using large commercial dairy herds and sufficient study power to evaluate milk production and reproductive responses to an enzyme treatment started during the precalving period. We hypothesized that the use of the enzyme treatment would increase milk production when provided to dairy cows precalving and for approximately 200 d of lactation. The study was conducted on 7,507 cows, in 8 replicates and 16 pens, at 3 dairies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, the current study is the first to report a significant interaction between enzyme supplementation and parity on lactational performance of dairy cows (other than the milk true protein concentration effect reported by Golder et al, 2019). An earlier study that evaluated the effects of fibrolytic enzymes and parity on feeding behavior, salivation, and ruminal pH demonstrated that primiparous cows consume feed more slowly and tend to ingest smaller amounts of feed during a feeding event than multiparous cows (Bowman et al, 2003; production data were not reported in that study).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…To the best of our knowledge, the current study is the first to report a significant interaction between enzyme supplementation and parity on lactational performance of dairy cows (other than the milk true protein concentration effect reported by Golder et al, 2019). An earlier study that evaluated the effects of fibrolytic enzymes and parity on feeding behavior, salivation, and ruminal pH demonstrated that primiparous cows consume feed more slowly and tend to ingest smaller amounts of feed during a feeding event than multiparous cows (Bowman et al, 2003; production data were not reported in that study).…”
Section: Resultsmentioning
confidence: 67%
“…For instance, enzyme dose (Holtshausen et al, 2011) and forage-toconcentrate ratio (Arriola et al, 2011) did not interact with parity to affect the performance of dairy cows. Golder et al (2019), in contrast, observed an enzyme × parity effect on milk protein concentration but no interactions for other production variables. Van Soest (1994) described a strong positive relationship between BW and the capacity of gastrointestinal tract in herbivores, which could be observed by limited meal size and reduced rate of feed intake in primiparous compared with multiparous cows (Bowman et al, 2003).…”
Section: Introductionmentioning
confidence: 59%
“…In dairy cows, the digestibility of dry matter and milk production has increased in diets with 34% silage of barley treated with fibrolytic enzymes (mixture of cellulase and xylanase) from Trichoderma reesei [45]. Recently, Golder et al [48] characterized the response in the field of the application of fibrolytic enzymes in supplemented dairy cows before delivery and for 200 days from the start of lactation in three dairy farms in the United States; eight randomly assigned pens were controlled without enzyme administration and eight more pens received a dose of 750 mL/t of feed for five months. The results showed that milk production increased with the enzymatic treatment to 0.70-0.80 kg/day, this could be due to the higher digestibility of the feed.…”
Section: Enzymes In Ruminant Feedsmentioning
confidence: 99%
“…Samples of all new deliveries, harvests, or batches of feeds were taken at each farm, along with periodic TMR samples from dairy 4, stored at −20°C and later analyzed by wet chemistry or near-infrared reflectance spectroscopy at Dairy One Cooperative Inc. Forage Testing Laboratory (Ithaca, NY) according to wet chemistry AOAC International (1999) methods detailed in Golder et al (2019). The near-infrared reflectance spectroscopy equations were based on methods detailed by Bramley et al (2012), with the exception of NDF, which was determined as described by Van Soest et al (1991), using heat-stable amylase without sodium sulfite and the NFC equation that was NFC = 100 − (NDF + CP + crude fat + ash).…”
Section: Dietmentioning
confidence: 99%